Exploring Human Health Benefits from Marine Biomedical Research with Fishes - Vidhya C.S.; Biswas , Susmi; Gangopadhyay , Sourav; Majumder , Jayeeta; Reddy , G Vidyasagar; Debnath , Abhijit; Magrey , Ashiq Hussain; Sivakumar , K. K.; Srivastava, Aparna; Afreen , Nadiya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Marine organisms, particularly fishes, harbor a treasure trove of bioactive compounds with immense potential for human health applications. In this review, we delve into the diverse array of bioactive molecules derived from marine fishes and their implications for biomedical research. We explore the therapeutic properties of fish-derived compounds, including antimicrobial peptides, omega-3 fatty acids, collagen, and bioactive peptides, among others andthe mechanisms of action and preclinical studies supporting the use of these compounds in various human health conditions, such as cardiovascular disease, cancer, inflammatory disorders, and neurodegenerative diseases. Additionally, we highlight the importance of sustainable sourcing and ethical considerations in marine biomedical research. Overall, this review underscores the significance of marine fishes as a source of novel therapeutic agents and the promising avenues they offer for advancing human health.